Growth of Tilapia (Oreochromis niloticus Linn.) Feeded by Fermented Coconut Pulp with Aspergillus niger - Sinaga, Lia Resa; Yanti, Ari Hepi; Setyawati, Tri Rima (Jurnal ILMU DASAR, 2024)
Coconut pulp fermented with Aspergillus niger can be used as an alternative ingredient in the manufacture of tilapia (O. niloticus) feed. This study aims to determine the nutritional content of fermented coconut dregs and the growth of tilapia after being fed a feed made from fermented coconut dregs with A. niger. Tilapia (O. niloticus) feed is made by mixing fermented coconut pulp and artificial feed. The combination of feed used in this study was A (control, 100% artificial feed), B (10% coconut pulp: 90% artificial feed), C (20% coconut pulp: 80% artificial feed), D (30% coconut pulp : artificial feed 70%), E (coconut pulp 40%: artificial feed 60%) and F (coconut pulp 50%: artificial feed 50%). Based on the proximate analysis that has been carried out, it shows that treatment B has the most optimal nutritional content for tilapia (O. niloticus). The nutritional content of feed B was 7.26% water content, 7.19% ash, 23,21% crude protein, 8,93% crude fat and 16,23% crude fiber. The results showed that treatment B gave the most significant growth rate and relative growth rate of 0.77 g/day and 3.04%.